The Role Of The Notary Deed Against Making Special Power Of Attorney To Say “Talaq” In Application Divorced In Religious Court - Dwi Indah Wahyuningsih; Heni Agustiningsih; Achmad Sulchan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The purpose of this study were: 1) to identify and analyze the role of the notary to manufacture special power of attorney notarized deed oath in filing for divorce in the Religious Court. 2) To identify and analyze the constraints notary in the manufacture of a special power of attorney notarized deed oath in filing for divorce in the Religious Court. The data used in this study are primary data, secondary data, and the data to support the assessment tertiary then analyzed with normative juridical method. Based on the results of data analysis concluded that: 1) In the implementation of the signing of the deed notarized power of special oath divorce in filing for divorce in the Religious of the parties, giving the power of attorney privilege and receiving power of attorney privilege to be present and facing the notary as the deed notarized letter The special power, because the authorizing unable to attend the oath of divorce in the Religious; 2) The provisions of the terms to make a notarized certificate of the applicant should include both the giver and the recipient of a special power of attorney and shown directly to the notary who will make the notary deed so that certificates can be made in accordance with existing procedures.Keywords: Notary; Special Power of Attorney; Notary Deed